Career decisions of international Chinese doctoral students: The influence of the self in the environment. (April 2018) - Lee, Myra CY; McMahon, Mary; Watson, Mark
In recent times, international research students from China have become a substantial demographic because aside from the revenue they bring to host countries, they are valued for their research contributions. To understand how to attract and support them, this article investigated the influences on the educational and post-graduation occupational decisions of Chinese doctoral research students based in Australia. These influences are interpreted within the Chinese relational context and the Systems Theory Framework. This article is based on research that interviewed 10 participants across three universities in Queensland, Australia, and thereafter, utilised thematic analysis as the analytical method. This article presents the derived themes relating to the influences of the self and the environment. The key findings highlight the interrelationships among the self, the family, cultural, and spiritual environment when making career decisions that balance personal aspirations against family expectations and societal constraints in order to maintain harmony.